Revitalizing Classical Islamic Learning: The Implementation of Classical Book-Based Teaching Materials in Islamic Education - Gofar, Abdul; Samrotul Ilmiyah (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2024)
Education is the primary foundation for shaping human character, morals, and life direction. In Islamic tradition, classical books (kutub al-turats) play an essential role as sources of knowledge and profound spiritual values. However, traditional teaching methods, still dominant in many Islamic educational institutions, often make it difficult for students to understand the contextual meanings and relevance of these books to modern life. This condition calls for innovation in the preparation of teaching materials that remain rooted in classical heritage but are presented with an approach that is adaptive to the needs of the times. This study aims to describe the implementation of the development of classical book-based teaching materials at MA Miftahul Qulub Gondang Mojokerto. The approach used is descriptive qualitative with research stages that include needs analysis, design, development, testing, and evaluation of teaching materials. Data were collected through observation, in-depth interviews, and documentation, then analysed using data reduction, data presentation, and verification techniques. Data validity was strengthened through triangulation of sources and methods. The results of the study show that MA Miftahul Qulub Gondang Mojokerto implements the Merdeka Curriculum, but Fiqh learning still relies on sources from classical texts (yellow books). The innovative teaching materials developed have been proven to significantly increase students' interest in learning and understanding classical texts. These findings confirm that integrating classical values with modern learning approaches can be an effective model for strengthening Islamic education that is relevant to the demands of the contemporary era.